Enhancement of Hybrid Beam Capacity with Glass Fiber Reinforced Polymer (GFRP): The Experimental Investigation into Metakaolin Substitution Effects - Salleh, Norhafizah; Puluhulawa, Indriyani (International Journal of Sustainable Construction Engineering and Technology, 2025)
The improvement of beam capacity is achievable through various alternatives, such as using high-strength concrete. However, enhancing concrete strength in beam without increasing the tensile reinforcement capacity can result in a smaller depth of concrete compression block (a). Reinforcing beam with high tensile strength (Ex. FRP) flexural reinforcement also has significant effects, causing an increase in flexural capacity. Previous investigations have established that concrete in the compression zone can fail before FRP reaches the yield point. This phenomenon shows the need for a combination of using flexural reinforcement with high tensile strength and substituting a portion of cement with metakaolin to produce higher-quality concrete. Therefore, this research aimed to investigate the influence of improving concrete quality using metakaolin on the flexural behavior of hybrid beam reinforced with GFRP. Two concrete variations were applied to four beams with dimensions of 200x250x3000 mm, consisting of two beams using normal grade 40 concrete, while the other two used grade 40 concrete with a 10% metakaolin substitution. Each variation used two different types of reinforcement, namely with and without GFRP as additional reinforcement and control beam, respectively. Subsequently, these beams were tested in a four-point bending configuration with a support span of 2500 mm. The results showed a 20.7% increase in cube strength, a 57.83% rise in ultimate flexural load, a 39.74% reduction in beam deflection, and a decrease in strain in concrete compression zone compared to control beam. Ductility was observed to be high as compressive strength (fcu) increased, while high reinforcement ratio resulted in a significant decrease.